Blockchain in Realistic Areas of Application and Difficulties Encountered: A Survey Study - Madhi, Mina H.; Al-Bakry, Abbas M.; Farhan, Alaa Kadhim (Iraqi Journal of Science, 2023)
Blockchain technologies have grown in popularity over the last few years, with various experts touting the technology’s potential applications in a range of businesses, markets, organizations, and governmental institutions. In the brief history of blockchain, an astounding number of incredible implementations have been done in terms of how it may be utilized and the potential effect it may have on a range of sectors. And, because of the great number and complexity of these characteristics, addressing the blockchain’s potential and complications can be difficult, especially when seeking to address its purpose and fit for a certain activity. The blockchain’s practical skills in fixing multiple challenges that are currently preventing further progress in various industrial fields are significant benefits. Securing and sharing transactional data, automating and optimizing supply chain procedures, and enhancing transparency throughout the value chain are just a few of the issues that companies are concerned about. Blockchain technology efficiently overcomes these challenges by leveraging distributed, shared, secure, and permission-based transactional ledgers. This paper concentrates on the many industrial application domains that blockchain technology offers. In addition, it examines and investigates the benefits, drawbacks, and challenges of incorporating blockchain into various industry applications, as well as defines the criteria for using blockchain in multiple industry applications and provides a brief overview of the technology.